2017
DOI: 10.5152/turkpediatriars.2017.4695
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical differences of influenza subspecies among hospitalized children

Abstract: Aim: Clinical findings, mortality, and morbidity rates differ among influenza subspecies. Awareness of these differences will lead physicians to choose the proper diagnostic and therapeutic strategies and to foresee possible complications. The aim of this study was to evaluate the clinical differences of influenza subspecies among hospitalized children. Material and Methods:Hospitalized children with proven influenza infection by polymerase chain reaction on nasopharyngeal swab specimens in our clinic, between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 25 publications
1
5
1
Order By: Relevance
“…Of these, more than three-quarters were infected with the influenza A virus, with the H1N1 pdm09 subtype being found in more than half the cases. The higher frequency of type A and, specifically, the H1N1 subtype, among cases admitted to the ICU, is in line with other published studies 1,2123 . This suggests disease severity is associated with influenza A infection, as in our study, in which the three deaths were caused by influenza A, and two by subtype H1N1 pdm09.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Of these, more than three-quarters were infected with the influenza A virus, with the H1N1 pdm09 subtype being found in more than half the cases. The higher frequency of type A and, specifically, the H1N1 subtype, among cases admitted to the ICU, is in line with other published studies 1,2123 . This suggests disease severity is associated with influenza A infection, as in our study, in which the three deaths were caused by influenza A, and two by subtype H1N1 pdm09.…”
Section: Discussionsupporting
confidence: 91%
“…1 who found that children with cancer were more susceptible to influenza B, and the study by Acar et al . 21 which found influenza B infection is more frequent in children with pulmonary, cardiac or immune system disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Of interest, CRP was not found to be as frequently elevated in mild COVID-19 cases as would be expected, yielding a PPE of only 18%. In children hospitalized with influenza, the rate of elevated CRP ranges from 37 to 67%) [33]. In contrast, we found an elevation in PCT level of 26% PPE, suggesting the possibility of a secondary bacterial infection in children hospitalized with COVID-19 pneumonia.…”
Section: Discussioncontrasting
confidence: 52%
“…In contrast, we found an elevation in PCT level of 26% PPE, suggesting the possibility of a secondary bacterial infection in children hospitalized with COVID-19 pneumonia. This is higher than that noted in children hospitalized with influenza, in which PCT elevations were noted in 6%-12% [33]. Importantly, bacterial and viral coinfections at the time of admission have been reported as being common in children with COVID-19 [24].…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation